SUBSTITUSI TEPUNG TERIGU DENGAN PANGAN LOKAL UBI UNGU (Ipomoea batatas L. Poir) DAN TEPUNG KACANG TANAH (Arachis hypogaea) PADA PEMBUATAN COOKIES : KAJIAN KADAR PROTEIN DAN MUTU ORGANOLEPTIK - Yahmi Ira Setyaningrum (ITKM WIDYA CIPTA HUSADA, 2021)
Cookies are one type of biscuit made from soft and dense textured dough. So far, cookies are made from wheat flour, so it is necessary to use local raw materials to explore food potential. In this study using purple sweet potato flour was used to substitute flour. The objective of this study was to analyze the effect of substitution of purple sweet potato flour and peanut flour on protein content and organoleptic quality in cookies. The study design was a randomized block design with 4 treatments, namely the proportion of purple yam flour: peanut flour namely F1 (55%: 20%), F2 (45%: 30%), F3 (35%: 40%). Protein content analysis used was the Kjeldahl method. Organoleptic quality uses a Hedonic Test. Statistical analysis uses Two Way Anova and DMRT with a confidence level of 95%. There is a significant effect of purple sweet potato flour and peanut flour (p = 0,000) on protein content in cookies. The highest protein content at F3 is 9.1%. The higher the addition of peanut flour, the higher the protein content in cookies. Statistical analysis used was Friedman with a confidence level of 95%. There was a significant effect of purple sweet potato flour and peanut flour (p = 0,000) on the level of cookies preferences (color, taste, aroma and texture). The most preferred formula from Hedonic Test was F3 in terms of color, taste, aroma, and texture of cookies.